Active Screen Event Detection in IoT Connected Android Devices - P. Shanmuga Prabha, Dr. S. Radha Rammohan,Ashwini.S, S.Magesh kumar (International Journal of Advanced Science and Technology, 2020)
Various cloud computing techniques faces problems nowadays because of hackers. Hackers have been looking for security vulnerabilities to abuse in Android applications. Such security vulnerabilities incorporate Android applications that could stack code at runtime which assists aggressors with maintaining a strategic distance from recognition by static investigation apparatuses. In this study, a broad examination is led so as to perceive how aggressors utilize refreshing procedures to endeavor such vulnerabilities, also, to survey the security dangers of utilizations in the commercial center utilizing these methods. A complete examination was conveyed out on about 30,000 applications gathered from three distinctive Android markets and two malware datasets. Static, dynamic and authorization based examinations were utilized so as to screen noxious exercises in such applications, and new malignant applications utilizing refreshing strategies were found in Google Play. The outcomes show that applications utilizing code refreshing methods are on the ascent. It is accepted this is the primary investigation of its sort to screen refreshing practices of uses during their execution. This examination permits us to profoundly dissect dubious applications and accordingly grow better security arrangements.